Reproductive factors and risk of melanoma: a population‐based cohort study4. (13th May 2019) - Støer, N.C.; Botteri, E.; Ghiasvand, R.; Busund, M.; Vangen, S.; Lund, E.; Veierød, M.B.; Weiderpass, E.
Summary: Background: The association between reproductive factors and risk of cutaneous melanoma (CM) is unclear. We investigated this issue in the Norwegian Women and Cancer cohort study. Objectives: To examine the association between the reproductive factors age at menarche, menstrual cycle length, parity, age at first and last birth, menopausal status, breastfeeding duration and length of ovulatory life, and CM risk, overall and by histological subtypes and anatomical site. Methods: We followed 165 712 women aged 30–75 years at inclusion from 1991–2007 to the end of 2015. Multivariable Cox regression was used to estimate hazard ratios (HRs) with 95% confidence intervals (CIs). Results: The mean age at cohort enrolment was 49 years. During a median follow‐up of 18 years, 1347 cases of CM were identified. No reproductive factors were clearly associated with CM risk. When stratifying by histological subtype we observed significant heterogeneity ( P = 0·01) in the effect of length of ovulatory life on the risk of superficial spreading melanoma (HR 1·02, 95% CI 1·01–1·04 per year increase) and nodular melanoma (HR 0·97, 95% CI 0·94–1·01 per year increase). When stratifying by anatomical site, menopausal status (HR 0·54, 95% CI 0·31–0·92, postmenopausal vs. premenopausal) and menstrual cycle length (HR 1·07, 95% CI 1·01–1·13, per day increase) were associated with CM of the trunk, and significant heterogeneity between anatomical sites was observed for menopausal status ( P = 0·04). Conclusions: In this large population‐based Norwegian cohort study, we did not find convincing evidence of an association between reproductive factors and risk of CM. Abstract : What's already known about this topic? Female sex hormones have been suggested to play a role in the aetiology of cutaneous melanoma (CM), and some epidemiological studies suggest that oestrogen increases the risk of CM. The association with endogenous sex hormones has been studied through various reproductive factors, and parity, age at menarche, age at first birth and length of ovulatory life have been found to be associated with the risk of CM. What does this study add? In this large nationwide population‐based study of the association between reproductive factors and CM risk, with detailed exposure and confounder information, no reproductive factors were clearly associated with CM risk. Associations between reproductive factors and histological subtypes and anatomical sites are scarcely described in the literature. We observed significant heterogeneity in the effect of length of ovulatory life on the risk of superficial spreading melanoma and nodular melanoma. Linked Comment:  Olsen. Br J Dermatol 2019;181 :239 . Plain language summary available online Respond to this article